Still Killing Mockingbirds: Narratives of Race and Innocence in Hollywood’s Depiction of the White Messiah Lawyer - Moore, Wendy Leo; Pierce, Jennifer (Qualitative Sociology Review, 2007)
Through a narrative analysis of movies confronting issues of race and racism in the post-civil rights era, we suggest that the movie To Kill a Mockingbird ushered in a new genre for movies about race which presented an image of a white male hero, or perhaps savior, for the black community. We suggest that this genre outlasted the era of the Civil Rights Movement and continues to impact popular cultural discourses about race in post-civil rights America. Post-civil rights films share the central elements of the anti-racist white male hero genre, but they also provide a plot twist that simultaneously highlights the racial innocence of the central characters and reinforces the ideology of liberal individualism. Reading these films within their broader historical context, we show how the innocence of these characters reflects not only the recent neo-conservative emphasis on “color blindness,” but presents a cinematic analogue to the anti-affirmative action narrative of the innocent white victim.